Логістичний підхід управління запасами в автосервісі - Морозюк, Сергій; Глінчук, Валерій (Посвіт, 2019)
The article investigates the system of spare parts inventory management using the logistic approach.
A logistics approach to inventory management in the automobile service station
Keywords: 629.113.004